Active Borders and Transnationalization of the Public Sphere in Europe: Examining Territorial and Symbolic Borders as a Source of Democratic Integration, Positive Identity, and Civic Learning. Issue 3 (August 2018) - Müller, Karel B.
This article suggests that both territorial and symbolic borders ought to be treated as specific cultural forms enabling the exercise and practice of cross-border communication. The notion of active border is introduced as a nexus of the transnationalization of public spheres and identities in Europe. Active border is interpreted as a border that supports and produces both public criticism and social integration without generating antagonism toward those from "over borders." Contrary to active border, passive border entrenches stereotypical negative identities and cognitive foreclosures and is a significant hindrance in positive identities formation. The concept of active border contributes to the broad sociological context of Europeanization and transnational public spheres and identities formations in which questions about cultural change and plurality should be discussed. It tries to offer a novel interpretative perspective on processes of transnationalization in Europe and beyond. This article draws inspiration mainly from Edward Shils's typology of collective identities, Erik Erikson's concept of identity formation, and Gerard Delanty's typology of cultural encounters.